KETERIKATAN KERJA PERAWAT: PENGARUH DUKUNGAN ORGANISASI, WORK-LIFE BALANCE DAN KEBAHAGIAAN - Dhurul Khoiriyah; Erita Yuliasesti Diah Sari; Herlina Siwi Widiana (Universitas Muhammadiyah Lampung, 2020)
Organizations always appreciate employees who have positive behavior, completion task, active, and committed to work. This study aims to examine the effect of organizational support and work-life balance on work engagement with happiness as a mediator variable. There were 122 nurses of a private hospital in Yogyakarta joint in this study. The data was collected through the Organizational Support Scale, Work-life Balance Scale, Happiness Scale, and Work Engagement Scale. Data analysis techniques with the SEM method with AMOS version 22.0. The results reveal that happiness is able to mediate the effect of organizational support and work-life balance on work engagement. The existence of organizational support as well as balance in life and work will foster happiness and promote positive behavior in organizations. Keywords: engagement, organizational support, work-life balance, happiness